Determinasi Keragaman Konsumsi Pangan dan Sanitasi Lingkungan sebagai Faktor Risiko Stunting - Alisa, Deby (Journal of Medical and Health Sciences, 2025)
Stunting remains a major nutritional issue in Indonesia, influenced by various multidimensional factors, including dietary patterns and environmental sanitation conditions. This study aims to analyze the determinants of food consumption diversity and environmental sanitation as risk factors for stunting in young children. The research design uses a cross-sectional approach with respondents aged 24–59 months selected purposively. Food consumption data were obtained through a food frequency questionnaire (FFQ), while environmental sanitation data were collected using a structured questionnaire. Data analysis was performed using logistic regression to examine the relationship between food consumption diversity, environmental sanitation, and the incidence of stunting. The results of the study show that low food consumption diversity is significantly associated with an increased risk of stunting (p < 0.05). Children with less diverse diets are more likely to experience stunting compared to those who consume a more varied diet. Furthermore, inadequate environmental sanitation conditions, such as limited access to clean water and poor waste disposal systems, also proved to be significant risk factors for stunting. These findings emphasize that stunting is not only related to nutritional intake but also influenced by environmental health conditions that support children's growth and development. This study concludes that efforts to prevent stunting should be integrated by improving both dietary diversity and environmental sanitation. Multisectoral interventions involving the health, agriculture, education, and environmental sectors are expected to sustainably reduce the prevalence of stunting in Indonesia.